2000
DOI: 10.1152/ajpcell.2000.278.3.c589
|View full text |Cite
|
Sign up to set email alerts
|

A myosin phosphatase targeting subunit isoform transition defines a smooth muscle developmental phenotypic switch

Abstract: Smooth muscle myosin phosphatase dephosphorylates the regulatory myosin light chain and thus mediates smooth muscle relaxation. The activity of this myosin phosphatase is dependent upon its myosin-targeting subunit (MYPT1). Isoforms of MYPT1 have been identified, but how they are generated and their relationship to smooth muscle phenotypes is not clear. Cloning of the middle section of chicken and rat MYPT1 genes revealed that each gene gave rise to isoforms by cassette-type alternative splicing of exons. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
101
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 53 publications
6
101
0
Order By: Relevance
“…We have identified splice variant isoform switching during smooth muscle phenotypic specification in avians and mammals in the embryonic and neonatal periods. This coincides with changes in smooth muscle function in the transition from fetal to adult physiology of the visceral and vascular systems (Dirksen et al 2000;Ogut and Brozovich 2000;Khatri et al 2001;Payne et al 2005). We are now focused on the myosin phosphatase targeting subunit 1 (MYPT1) alternative exons as a model to identify control mechanisms for developmental specification of smooth muscle phenotypes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have identified splice variant isoform switching during smooth muscle phenotypic specification in avians and mammals in the embryonic and neonatal periods. This coincides with changes in smooth muscle function in the transition from fetal to adult physiology of the visceral and vascular systems (Dirksen et al 2000;Ogut and Brozovich 2000;Khatri et al 2001;Payne et al 2005). We are now focused on the myosin phosphatase targeting subunit 1 (MYPT1) alternative exons as a model to identify control mechanisms for developmental specification of smooth muscle phenotypes.…”
Section: Introductionmentioning
confidence: 94%
“…In smooth muscle, isoforms of a number of key contractile proteins are generated by alternative splicing of exons, including myosin heavy (Babij and Periasamy 1989;Kelley et al 1993) and light chains (Nabeshima et al 1987;Helper et al 1988), myosin phosphatase (MP) (Shimizu et al 1994;Johnson et al 1997;Dirksen et al 2000), tropomyosin (Wieczorek et al 1988), caldesmon (Ueki et al 1987), calponin (Samaha et al 1996), and others (for review, see Sobue et al 1999). The tissue-specific expression of these splice-variant isoforms in fast-phasic versus slow-tonic contractile smooth muscle phenotypes (Somlyo and Somlyo 1968) are thought to determine organ function in development and disease (for review, see Owens et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Features of the MYPT1 molecule (using the rat 1 isoform [2] as a model; this has no central exon deletions and is LZ+) show a PP1c-binding motif, often referred to as the RVXF motif (consensus sequence (R/K)X 1 (V/I)X 2 (F/W)) at the N-terminal edge (residues 35-38) of eight ankyrin repeats spanning residues 39-296. Two nuclear localization sequences (NLS) are present in both N-and C-terminal regions, residues 27-33 and 845-854, respectively.…”
Section: Properties Of Mypt1mentioning
confidence: 99%
“…Several isoforms can be generated by cassette-type alternative splicing and these represent the presence or absence of central inserts (exons 13 and 14 in rat) and/or the C-terminal leucine zipper (LZ) motifs (splicing of exon 23). To some extent the expression pattern of these isoforms is tissue specific [2]. For the central insert isoforms, there is no clear distinction in function.…”
mentioning
confidence: 99%
“…1A) contains two putative COOH-terminal coiled-coil (CC) domains at aa 715-746 and aa 929 -969, which have 60% and 81% probabilities of CC formation, respectively (16), and a third domain at aa 1013-1039, which is known as the leucine zipper (LZ) (12). These sequences are numbered according to the M133 MYPT1 isoform sequence reported by Shimizu et al (21), which is central insert (CI) positive (CIϩ, aa 512-553), whereas the M130 isoform, which is expressed in chicken gizzard, is CI negative (CIϪ); therefore, numbering of the sequences is displaced toward the NH 2 terminus by 41 amino acids (5,21). Studies with glutathione S-transferase (GST)-fusion peptides have demonstrated that the NH 2 -terminal LZ of PKGI␣ (24) and COOH-terminal LZ of MYPT1 (23) are important for the PKGI␣-MYPT1 interaction.…”
mentioning
confidence: 99%